2018
DOI: 10.1029/2017jc013307
|View full text |Cite
|
Sign up to set email alerts
|

Winter Water Formation in Coastal Polynyas of the Eastern Chukchi Shelf: Pacific and Atlantic Influences

Abstract: Water properties and formation processes of Alaskan Coastal Winter Water (ACWW) over the eastern Chukchi shelf along the Alaska coast, the so‐called Barrow Canyon pathway, are examined using data from moorings, atmospheric reanalysis, satellite‐derived sea‐ice production (SIP), and a numerical tracer experiment. Along this pathway, Pacific Winter Water (PWW) can be modified to produce ACWW through SIP accompanied by production of cold, saline polynya water in the coastal polynyas, upwelling of warm Atlantic Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Accumulated IP ranges between 25 and 125 km 3 per winter, and likewise to POLA there are no significant trends. Supporting that finding, Hirano et al () also found an absence of any significant trend or transition in the magnitude of IP between 1992 and 2014, and postulated that the year‐to‐year variability in IP is related to varying winter northeasterly wind stress. Derived metrics from AMSR‐E and MODIS agree very well, with only 4% to 8% difference for both POLA and IP (Tables and ).…”
Section: Long‐term Comparison Of Thin‐ice Frequencies and Ipmentioning
confidence: 85%
See 2 more Smart Citations
“…Accumulated IP ranges between 25 and 125 km 3 per winter, and likewise to POLA there are no significant trends. Supporting that finding, Hirano et al () also found an absence of any significant trend or transition in the magnitude of IP between 1992 and 2014, and postulated that the year‐to‐year variability in IP is related to varying winter northeasterly wind stress. Derived metrics from AMSR‐E and MODIS agree very well, with only 4% to 8% difference for both POLA and IP (Tables and ).…”
Section: Long‐term Comparison Of Thin‐ice Frequencies and Ipmentioning
confidence: 85%
“…Similar to the Laptev Sea, the Chukchi Sea has been subject to a huge number of in situ, remote sensing and modeling studies related to sea ice and dense‐water formation (Cavalieri & Martin, ; Fukamachi et al, ; Hirano et al, , ; Iwamoto et al, , ; Martin et al, , ; Tamura & Ohshima, ; Weingartner et al, ; Winsor & Björk, ; Winsor & Chapman, , among various others). Regular forming coastal polynyas appear along the Alaskan coastline due to strong offshore winds from northerly to easterly directions, most frequently around Point Barrow in the north over to Wainwright and Icy Cape down to Cape Lisburne in the south.…”
Section: Long‐term Comparison Of Thin‐ice Frequencies and Ipmentioning
confidence: 99%
See 1 more Smart Citation
“…Aksenov et al, 2016;Jones, 2001;McLaughlin et al, 2002;Steele et al, 2004;Timmermans et al, 2014). In this special collection, Spall et al (2018), Zhong et al (2019), Hirano et al (2018), and Hu and Myers (2019) discuss the most recent findings associated with the circulation of the Pacific water layers and factors influencing their dynamics and properties.…”
Section: Introductionmentioning
confidence: 99%
“…The coastal polynya system of the northeastern Chukchi Sea along the Alaskan coast, with significant wind‐driven offshore ice transport, has been identified as a major source of ice production (Martin et al, , ; Tamura & Ohshima, ; Iwamoto et al, ; Figure ). Saline water, that is, brine, excluded from growing sea ice in these polynyas results in dense water, which contributes to formation of the cold halocline layer in the Arctic Ocean (Hirano et al, ; Itoh et al, ; Martin et al, ). Previous work, tracing back highly sediment laden ice based on ice drift trajectories from buoys and a simple model, indicates significant particle entrainment into sea ice in this region (Eicken et al, ).…”
Section: Introductionmentioning
confidence: 99%